安全剂用于提高水稻作物对除草剂的抗性的用途 (2023)
本发明提供了一种用于防治在抗除草剂的水稻作物附近的不想要的植物的除草混合物，其中所述除草混合物包含：a)抑制乙酰辅酶A羧化酶(ACCase)的除草剂或抑制4-羟苯基丙酮酸双加氧酶(HPPD)的除草剂或抑制乙酰乳酸(乙酰羟酸)合酶ALS(AHAS)的除草剂或其组合，和b)除草剂安全剂，其选自双苯噁唑酸、喹氧乙酸、AD-67、解草酮和解草啶以及其酯、盐及其组合。本发明还提供了包含本文公开的除草混合物的组合物，以及使用本文公开的除草混合物和组合物防治水稻作物附近的不想要的植物的方法。 The subject invention provides a herbicidal mixture for controlling undesired vegetation in the vicinity of an herbicide resistant rice crop, wherein the herbicidal mixture comprises a) an acetyl Co-A carboxylase (ACCase) inhibiting herbicide or a 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibiting herbicide or an acetolactate (acetohydroxy acid) synthase ALS (MIAS) inhibiting herbicides or combinations thereof and b) an herbicide safener selected from isoxadifen, cloquintocet, AD-67, benoxacor and fenclorim, and esters, salts and combinations thereof. The present invention also provides compositions comprising the herbicidal mixtures disclosed herein and methods of controlling undesired vegetation in the vicinity of a rice crop using the herbicidal mixtures and composi